2022
DOI: 10.3390/ijerph19159628
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Pediatric Patients with Continent Urinary Diversion—A Single Center Experience

Abstract: Background and Objectives: The advancement of surgical strategies in various types of urological conditions has resulted in improved functional outcomes, but the issues of patient perception and life quality remain difficult to assess, particularly in pediatric populations. We aimed to critically analyze the outcomes of urinary continent diversion in pediatric patients treated in our institution for various bladder conditions. Materials and Methods: We conducted a cross-sectional study, reviewing the records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, the disadvantages of amputating a healthy appendix as opposed to performing an enterotomy without bowel resection should be weighed against salvage appendectomy. Appendectomy should be avoided in children with anorectal malformations or other medical conditions that are associated with fecal or urinary incontinence, as the appendix may be needed in such children as a urinary conduit or as a conduit for antegrade enemas [ 22 , 23 ]. In addition, a number of recent studies suggest that the appendix has several significant physiological roles, such as production of mesenchymal stem cells [ 24 ] and functioning as a reservoir for commensal bacteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the disadvantages of amputating a healthy appendix as opposed to performing an enterotomy without bowel resection should be weighed against salvage appendectomy. Appendectomy should be avoided in children with anorectal malformations or other medical conditions that are associated with fecal or urinary incontinence, as the appendix may be needed in such children as a urinary conduit or as a conduit for antegrade enemas [ 22 , 23 ]. In addition, a number of recent studies suggest that the appendix has several significant physiological roles, such as production of mesenchymal stem cells [ 24 ] and functioning as a reservoir for commensal bacteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continent urinary diversion as an effective and durable treatment can be offered to well-selected older pediatric NLUTD for whom transurethral CIC is not feasible. 84 Recent reports and reviews described that patients on continent catheterizable channels have a good overall quality of life and associated patient satisfaction; [85][86][87] However, relatively common long-term reintervention rates and comorbidities may need to be discussed preoperatively with the patient and family to ensure an informed decision. 88 Congregated evidence generated by the NICE and SBA guidelines, as well as recent reports, has shown that augmentation cystoplasty improves bladder capacity and reduced detrusor pressure, decreasing the likelihood of incontinence, specifically in older pediatric patients with NLUTD.…”
Section: █ Recommendation 12: Vesicostomy (Weak Recommendation Le Iii...mentioning
confidence: 99%
“…The suggested method estimates the anatomical structures by resolving a constrained optimization problem that combines wavelet-domain sparsity and total variation (wavelet-TV) regularization in order to preserve the edges of retinal layers and lessen artifacts brought on by pure wavelet thresholding. To accomplish the goal function outlined in [ 17 , 18 ], we use a brand-new hybrid approach called the Randomized FireFly (FF) update in Lion Algorithm (RFU-LA), which includes components of both the Lion Algorithm (LA) and the FireFly Algorithm (FF). By taking the mean of images that have been routinely median-filtered using different kernel sizes, the hybrid median-mean filter (HM2F) proposed in [ 19 ] is a one-shot image processing method for decreasing speckle noise.…”
Section: Related Workmentioning
confidence: 99%